Evaluation of vitamin-producing and immunomodulatory lactic acid bacteria as a potential co-adjuvant for cancer therapy in a mouse model - Levit, Romina (2021)
Aims: To evaluate a mixture of selected lactic acid bacteria (LAB) (a riboflavin-producer, a folate-producer and an immunomodulatory strain) as co-adjuvant for 5-fluorouracil (5-FU) chemotherapy in cell culture and using a 4T1 cell animal model of breast cancer. Methods and results: The viability of Caco-2 cells exposed to 5-FU and/or LAB was analysed. Mice bearing breast tumour were treated with 5-FU and/or LAB. Tumour growth was measured. Intestinal mucositis (IM) was evaluated in small intestine; haematological parameters and plasma cytokines were determined. The bacterial mixture did not negatively affect the cytotoxic activity of 5-FU on Caco-2 cells. The LAB mixture attenuated the IM and prevented blood cell decreases associated with 5-FU treatment. Mice that received 5-FU and LAB mixture decreased tumour growth and showed modulation of systemic cytokines modified by both tumour growth and 5-FU treatment. The LAB mixture by itself delayed tumour growth. Conclusions: The mixture of selected LAB was able to reduce the side-effects associated with chemotherapy without affecting its primary anti-tumour activity. Significance and Impact of the Study: This bacterial mixture could prevent the interruption of conventional oncologic therapies by reducing undesirable side-effects. In addition, this blend would provide essential nutrients (vitamins) to oncology patients.